The Use of a Novel Super-Oxidized Solution on Top of Standard Treatment in the Home Care Management of Postsurgical Lesions of the Diabetic Foot Reduces Reinfections and Shortens Healing Time. (December 2018) - Iacopi, Elisabetta; Abbruzzese, Lorenza; Goretti, Chiara; Riitano, Nicola; Piaggesi, Alberto
There are still many unmet needs in the treatment of chronic wounds, especially regarding microenvironment modulation. Nexodyn is a novel super-oxidized solution capable of contrast bacterial proliferation. We aimed to evaluate if this solution, on top of standard of care, was safe and effective in improving diabetic foot outcome. We selected 50 patients admitted in our department to be submitted to surgery for acute diabetic foot infection. All patients were left open to heal for secondary intent. We divided patients into 2 groups: Group A (n = 25, male/female = 17/8, age = 67.3 ± 12.1 years, hemoglobin A1C = 7.9 ± 1.1%), patients treated with standard of care and, on top of this, Nexodyn solution, and Group B, treated only with standard of care. After discharge, patients continued Nexodyn application. We followed up patients until complete healing or up to 6 months. No differences between groups in healing rate, while time required for complete healing was significantly shorter in Group A (64.9 ± 12.1 days vs 147.4 ± 23.1 days, P < .01). During follow-up, the group treated with Nexodyn showed a reduced rate of reinfections (12 patients in Group B vs 3 patients in Group A, P < .05) and of further debridement procedures (1 patient in Group A vs 10 patients in Group B, P < .05). Nexodyn provided effective protection against reinfections in diabetic foot patients, thus reducing the necessity for debridement procedures and their healing time and presents a safety profile similar to saline solution.